2013
DOI: 10.1200/jco.2012.44.8738
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Placebo-Controlled Trial of Acetyl-L-Carnitine for the Prevention of Taxane-Induced Neuropathy in Women Undergoing Adjuvant Breast Cancer Therapy

Abstract: A B S T R A C T PurposeChemotherapy-induced peripheral neuropathy (CIPN) is common and leads to suboptimal treatment. Acetyl-L-carnitine (ALC) is a natural compound involved in neuronal protection. Studies have suggested ALC may be effective for the prevention and treatment of CIPN. Patients and MethodsA 24-week randomized double-blind trial comparing ALC (3,000 mg per day) with placebo in women undergoing adjuvant taxane-based chemotherapy was conducted. The primary objective was to determine if ALC prevents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
125
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(135 citation statements)
references
References 32 publications
1
125
0
9
Order By: Relevance
“…The Southwest Oncology Group (SWOG) S0715 study has contradicted initial optimism after evaluating the role of Alcar in preventing CIPN in 409 patients receiving taxanes during adjuvant breast cancer therapy. With regard to control group, there has been a trend to worsening neurological symptoms in the intervention group after 24 weeks of follow-up 36 . A randomized placebo-controlled study has evaluated the efficacy of baclofen (10mg), amitriptyline (40mg) and ketamine (20mg) in a lecithin in organogel (BAK-OLP) versus placebo (OLP) to treat CIPN during 4 weeks in 208 patients.…”
Section: Management and Preventionmentioning
confidence: 99%
“…The Southwest Oncology Group (SWOG) S0715 study has contradicted initial optimism after evaluating the role of Alcar in preventing CIPN in 409 patients receiving taxanes during adjuvant breast cancer therapy. With regard to control group, there has been a trend to worsening neurological symptoms in the intervention group after 24 weeks of follow-up 36 . A randomized placebo-controlled study has evaluated the efficacy of baclofen (10mg), amitriptyline (40mg) and ketamine (20mg) in a lecithin in organogel (BAK-OLP) versus placebo (OLP) to treat CIPN during 4 weeks in 208 patients.…”
Section: Management and Preventionmentioning
confidence: 99%
“…More encouraging results were obtained with the administration of all-trans retinoic acid in an animal model and patients with lung cancer [33]. Conversely, acetyl-L-carnitine increased CIPN at 24 weeks compared with placebo although no difference was observed at 12 weeks in women undergoing adjuvant breast cancer therapy [34]. New alternative therapies have been considered for prevention of CIPN and there is considerable interest in the prophylactic role of natural products, such as curcumin [35], matricaria chamomilla [36], ginkgo biloba extract [37], and green tea [38].…”
mentioning
confidence: 58%
“…Yet a recent concern over L-carnitine utilization by potentially heart disease producing flora received attention [46], but so did a meta-analysis demonstrating a lower risk of cardiovascular events with L-carnitine from secondary prevention studies [47]. Another recent phase 3 trial in cancer to reduce chemotherapy induced neuropathy actually found an increase in neuropathy with this supplement at 3,000 mg per day [48]. Therefore, the controversy of whether or not this supplement could be beneficial will continue.…”
Section: L-carnitinementioning
confidence: 94%